2019
DOI: 10.1210/jc.2019-00195
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Agents in Older Individuals: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Background The efficacy of lipid-lowering agents on patient-important outcomes in older individuals is unclear. Methods We included randomized trials that enrolled individuals aged 65 years or older and that included at least 1 year of follow-up. Pairs of reviewers selected and appraised the trials. Results We included 23 trials that enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
1
22
2
2
Order By: Relevance
“…77 In a meta-analysis of nine primary prevention trials that enrolled patients 65 years or older, though statins reduced the incidence of CAD events for those 65 years or older, there was no significant reduction for those 75 years and older. 66 However, in a meta-analysis of the JUPITER and HOPE-3 trials, the authors concluded that the results support the use of statins to prevent CVD for older adults with low to intermediate CVD risk, up to at least 80 years of age. The recommendation is based on a reduction in the composite measure of nonfatal MI, nonfatal stroke, and CVD death.…”
Section: Lipid-lowering Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…77 In a meta-analysis of nine primary prevention trials that enrolled patients 65 years or older, though statins reduced the incidence of CAD events for those 65 years or older, there was no significant reduction for those 75 years and older. 66 However, in a meta-analysis of the JUPITER and HOPE-3 trials, the authors concluded that the results support the use of statins to prevent CVD for older adults with low to intermediate CVD risk, up to at least 80 years of age. The recommendation is based on a reduction in the composite measure of nonfatal MI, nonfatal stroke, and CVD death.…”
Section: Lipid-lowering Agentmentioning
confidence: 99%
“…Though there is no evidence that lipid-lowering agents help prevent incident stroke in older adults, 66 as discussed in the section below on preventing CAD, there are data that support the use of statins to prevent composite CVD outcomes in older adults who do not have a history of CVD, up to 80 years of age.…”
Section: Lipid-lowering Agentsmentioning
confidence: 99%
“…Ponce et al performed a comprehensive meta-analysis of 23 RCTs comprising 60,194 patients aged 65+ [ 72 ]. Cohort data was collated for each of five patient groups: ages 65–75, ages 75 and over, patients with diabetes, patients without diabetes, and patients with hypertension.…”
Section: Efficacy Of Statin Treatment In the Elderlymentioning
confidence: 99%
“…For primary prevention in those with no history of ASCVD, statin use was found to reduce the risk of coronary artery disease [CAD; RR: 0.79, 95% CI: 0.68–0.91] and myocardial infarction (RR: 0.45, 95% CI: 0.31–0.66) relative to placebo in all patient groups. However, Forest plot analysis revealed that statins did not significantly reduce the risk of heart failure (RR: 1.04, 95% CI: 0.80–1.35), all-cause mortality (RR: 0.95, 95% CI: 0.84–1.07), or cardiovascular mortality (RR: 1.01, 95% CI: 0.83–1.24) overall or in any patient group [ 72 ]. The one RCT of adults ≥75 reported an increase in all-cause mortality for 40 mg/day pravastatin vs. usual care (HR: 1.34, 95% CI: 0.98–1.84) [ 73 ].…”
Section: Efficacy Of Statin Treatment In the Elderlymentioning
confidence: 99%
See 1 more Smart Citation